1985
DOI: 10.1093/sleep/8.4.347
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Development of Sleep-Wake Patterns in Sheep

Abstract: Chronic intrauterine monitoring of electrocortical activity, eye movements, and electromyographic activity of the nuchal muscles has permitted the use of established polygraphic criteria to study the ontogenetic development of organized sleep-wake patterns in the fetal lamb in utero. Sixty-five polygraphic recordings obtained from 21 fetal lambs ranging from 112 to 144 days of gestation (term = 145 days) were analyzed. The results show that the transition from disorganized to organized behavioral state pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
71
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(78 citation statements)
references
References 14 publications
6
71
1
Order By: Relevance
“…In utero sleep is prominently exhibited by all mammalian prenatals that have been carefully observed (Ruckebusch 1972;Drucker-Colín et al 1979;Awoust and Levi 1984;Szeto and Hinman 1985). Human fetal sleep begins early in the third trimester of pregnancy.…”
Section: The Dolphin Dilemmamentioning
confidence: 99%
“…In utero sleep is prominently exhibited by all mammalian prenatals that have been carefully observed (Ruckebusch 1972;Drucker-Colín et al 1979;Awoust and Levi 1984;Szeto and Hinman 1985). Human fetal sleep begins early in the third trimester of pregnancy.…”
Section: The Dolphin Dilemmamentioning
confidence: 99%
“…Electrocortical activity can be detected in prenatal life and has been shown to undergo maturational changes throughout late gestation. These developmental changes include the progression from an immature waveform pattern of variable frequencies to the typical HVSA and LVFA patterns described by a number of investigators (1 -6); changes in the relative incidence of these two predominant patterns (2, 6); as well as maturational changes in the waveform characteristics of the two predominant patterns (5,6).…”
mentioning
confidence: 99%
“…These discrepancies in fetal behavioral state might have been because of the different criteria used to define fetal arousal as well as different techniques to induce continuous breathing. Most investigators have used the electrographic criteria to define the fetal sleep states (6,7), whereas Rigatto (34) observed the fetus through a Plexiglas window implanted in the ewe's left flank. However, no studies comparing the electrographic and visual observation have been reported in a chronically prepared fetal sheep.…”
Section: Discussionmentioning
confidence: 99%
“…Breathing stopped at a Pao2 of 38.5 +: 9.5 torr (5.1 f 1.3 kPa) but could be restarted by increasing the Pao2. In response to an increase in fetal Pao, (4)(5)(6)(7)(8), amplitude of breathing and total respiratory output significantly increased from the control values. Further increases in Pao2 or Hb O2 saturation did not significantly affect the respiratory output.…”
mentioning
confidence: 86%
See 1 more Smart Citation